2005
DOI: 10.1103/physreve.72.025602
|View full text |Cite
|
Sign up to set email alerts
|

Non-Gaussian statistics of optical near-fields

Abstract: Optical fields in the proximity of random media can be modeled as a superposition of waves with random phases. We demonstrate that, depending on the experimental geometry, both Gaussian and non-Gaussian regimes can be established for the statistics of scattered intensity. In a reflection-emission configuration, the first-order statistics of the scattered light is non-Gaussian and it can be used to retrieve information about the physical interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…In particular, the intensity-intensity spatial correlation function is linearly related to the spatial autocorrelation function of the surface profile, thus exhibiting a high degree of non-universality. Another study has shown differences between near-field speckles produced by an illumination in transmission through a thick sample in the multiple scattering regime, and by a local illumination in reflection on the same sample [84]. Deviations from the Rayleigh statistics for the intensity distribution have been observed, indicating that the hypotheses of a fully developed speckle could break down.…”
Section: Other Evidences Of Non-universality In Near-field Specklesmentioning
confidence: 96%
See 1 more Smart Citation
“…In particular, the intensity-intensity spatial correlation function is linearly related to the spatial autocorrelation function of the surface profile, thus exhibiting a high degree of non-universality. Another study has shown differences between near-field speckles produced by an illumination in transmission through a thick sample in the multiple scattering regime, and by a local illumination in reflection on the same sample [84]. Deviations from the Rayleigh statistics for the intensity distribution have been observed, indicating that the hypotheses of a fully developed speckle could break down.…”
Section: Other Evidences Of Non-universality In Near-field Specklesmentioning
confidence: 96%
“…SNOM studies of near-field speckles have been reported in Refs. [82,83,84,85]. An example of far-field and near-field speckle produced by a strongly scattering material is shown in Fig.…”
Section: Near-field Microscopy On Disordered Dielectricsmentioning
confidence: 98%
“…According to assumptions given in [17], the reference wave that should be also linearly polarized in incidence plane is used for modulation visualization of polarization distribution. The experimental realization of such interaction is presented in [21], where contribution of polarization constituent in general degree of correlation of interactive fields is demonstrated. Fig.…”
Section: Model Presentation Of Interaction Of Two Mutually Orthogonalmentioning
confidence: 99%
“…The interaction of orthogonal linearly polarized waves is characterized by occurrence of strongly focused modes of laser radiation causing amplification, and thus, the necessity of consideration of longitudinal component of resultant distribution. The mechanism of the formation of longitudinal field component is typical for near diffraction zone allowing effective using of generated z-component in tasks of spectral diagnostics of single molecules, organelles and cells [21,22]. According to assumptions given in [17], the reference wave that should be also linearly polarized in incidence plane is used for modulation visualization of polarization distribution.…”
Section: Model Presentation Of Interaction Of Two Mutually Orthogonalmentioning
confidence: 99%
“…The practical importance of this problem is increasing owing to the development of techniques based on confocal microscopy of isolated molecules, including long molecules oriented along the direction of beam propagation, and due to systems for 3D imaging of such molecules [7], where knowledge about the z-component of the field is absolutely necessary [8]. In general, such situations occur in problems like:…”
Section: Introductionmentioning
confidence: 99%